Prevention of Dry Eye Syndrome Before Phacoemulsification of Cataracts in Patients with a History of Cosmetic Procedures in the Periorbital Area - А. V. Trubilin; E. G. Poluninа; V. N. Trubilin; V. S. Zakatianskii (Oftalʹmologiâ)
Phacoemulsification of cataracts in modern ophthalmological practice has reached its peak in terms of safety, predictability of the result and patient satisfaction with the result obtained. The effect of dry eye syndrome on the effectiveness of this surgical intervention has been studied to a large extent, but new risk factors affecting the development of dry eye syndrome arise, such as cosmetic intervention in the periorbital zone (botulinum toxin injections in the periorbital zone, eyelash extensions, blepharoplasty). The effect of these risk factors for the development of dry eye syndrome (DES) on the course of the postoperative period has not been sufficiently studied. An important aspect in preparing patients for ophthalmic surgery, in particular, for phacoemulsification of cataracts, which has moved into the category of, among other things, refractive surgeries, is stabilization of the ocular surface and relief of signs and symptoms of DES.Materials and methods. The study included 117 patients who were planned to undergo phacoemulsification of cataracts. All 117 patients were female for the unification of the study. The first group included 85 people with risk factors for developed dry eye syndrome (botox, tattooing, eyelash extensions, blepharoplasty) in the preoperative period of at least 3 years after cosmetology intervention in the periorbital area. The second control group included 32 patients without risk factors for development in the form of cosmetology intervention in the periorbital area in the preoperative period. The first group was divided into 3 subgroups depending on the type of patient preparation for surgery: 1A (main group) — 30 patients: tear replacement therapy without complex therapy (eyelid hygiene according to the developed technique + massage in the periorbital area), 1B — 29 patients: tear replacement therapy + complex therapy according to the developed technique; 1B — 26 patients: tear replacement therapy + complex therapy according to the standard technique. As the study showed, in the presence of risk factors for the development of dry eye syndrome in the preoperative period before phacoemulsification, including a history of cosmetic interventions in the periorbital area, an increased risk of developing a severe form of dry eye syndrome and an inflammatory process in the early postoperative period was noted at a 2-week observation period. This group of patients is recommended to undergo a set of therapeutic physiotherapeutic procedures — eyelid hygiene + massage in the periorbital area, aimed at restoring the functional activity of the meibomian glands and increasing the stability of the tear film, which reduces the incidence of severe dry eye syndrome and inflammation in the postoperative period after cataract phacoemulsification by 19.89%.